Mapping resilience: Development of the resilience process scales (RPS) and resilience profiles during adversity - Joseph Anthony Pettit; Stuart Beattie; Ross Roberts; Nichola Callow (PLoS ONE, 2026)
The resilience literature is often criticised for lacking clarity in the conceptualisation and measurement of resilience, with the literature yet to consider within-person profiles of resilience and how such profiles might influence reactions to different adverse contexts. To significantly enhance the research area, the current set of studies propose and test a four-stage process model of resilience including proactive (anticipation & minimizing) and reactive (managing & mending) components. We suggest the four processes can function independently within five separate domains (general, physical, social, cognitive, and emotional). Specifically, in Studies 1 ( n = 181) and 2 ( n = 284) we develop a measure of resilience reflecting our four-stage process model and demonstrated validity of a 13-item measure for each of the five proposed domains via a Bayesian structural equation modelling approach. Focusing on the general domain and based on the four resilience processes (anticipate, minimize, manage, & mend), Study 3 ( n = 400) explored resilience profiles in a pilot study, and then confirmed these profiles and their relationship with psychological and behavioral outcomes related to the COVID-19 pandemic in a main study. Using latent profile and latent transition analysis, results revealed four distinct profiles, predicting a range of psychological outcomes. For example, those with lower resilience (particularly profiles with high anticipation but low levels of the other processes), showed higher anxiety (especially with high anticipation), depression, impulsiveness, and lower coping effectiveness. Those with higher resilience (Profile 3 and 4) across the four processes exhibited lower depression, anxiety, and impulsiveness, as well as higher well-being, better perceived coping effectiveness, and preventative behaviors. Taken together the results from the studies presented, support the process model of resilience and underscore the benefits of considering resilience profiles in relation to understanding how people deal with adverse contexts.